EFFECTIVENESS OF ZINC SUPPLY ON WEIGHT INCREASE IN TODDLERS AGED 2-5 YEARS AT TPMB INDRA WAHYU - Riza Tsalatsatul Mufida; Nur Afidatul Fajriyah (Universitas STRADA Indonesia, 2025)
This issue deterioration occurs, it can be said to be malnutrition and is usually characterized by weight loss and stunted development. This study aims to determine the effectiveness of zinc administration on increasing the weight of toddlers aged 2-5 years at TPMB Indra Wahyu. The Quasi-experimental with a pre-test - post-test design. Purposive sampling technique. The sample is 52 respondents. From toddlers aged 2-5 years. Variable (X) Zinc Syrup. Variable (Y) Weight Gain. This research using the Wilcoxon Test. The results of the study after the intervention for 30 days, most experienced an increase in body weight of 32 children (82%) and those whose body weight remained the same as 7 children (18%). Test statistical test obtained p = 0.001 so that p <0.05 and there is effectiveness in providing zinc syrup on increasing the weight of toddlers aged 2-5 years at TPMB Indra Wahyu.